Anti-inflammatory Activities of Methyl trans-Cinnamate derivatives on Carrageenan-Induced Paw Edema in Male Sprague Dawley Rats - Ernawati, Teni; Yuliani, Tri; Minarti, M; Dewijanti, Indah Dwiatmi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The purpose of this study was to evaluate the anti-inflammatory activity of cinnamic acid and 3-phenyl propanoic acid and also virtual screening of the methyl trans-cinnamate derivatives were carried out on the COX-2 enzyme.Methodology: The cinnamic acid and 3-phenylpropanoic acid were tested for anti-inflamatory activity in vivo using carageenan-induced rat paws edema method. Thirty male Sprague-Dawley rats were divided into 5 groups: control group, Na diclofenac (0.45 mg/kg body weight), ibuprofen (7.2 mg/kg body weight ), cinnamic acid (14.4 mg/kg body weight) and 3-phenyl propionate acid (14.4 mg/kg body weight). Paw edema was observed using a plethysmometer for 46 hours, these were at 0, 0.5, 2, 3, 4, 5, 22, 29 and 46 hours. Each compound of methyl trans-cinnamate derivatives to be performed molecular docking, virtual constructed in the form of two-dimensional (2D) using BKChem application. The simulation molecular docking using PLANTS 1.1. The structure of methyl trans-cinnamate derivatives was characterized by IR, melting point, UV, 1H NMR, 13C NMR, and mass spectral analysis. Results: The result showed that antiinflamatory activity of Na diclofenac, ibuprofen, cinnamic acid, and 3-phenil propionic acid were -20,6 %, -3,7 %, -43,2 %, 27,7 % respectively. These results showed only 3-phenil propionic acid could reduce edema in the rats’ paw. The docking results show that cinnamic acid, 3-phenyl propanoic acid and 3- (4-benzoylphenyl) propanoic acid are predict to have activity as COX-2 inhibitors.